1998
DOI: 10.1073/pnas.95.25.14886
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic knockout mice exclusively expressing human hemoglobin S after transfer of a 240-kb β s -globin yeast artificial chromosome: A mouse model of sickle cell anemia

Abstract: Sickle cell anemia (SCA) and thalassemia are among the most common genetic diseases worldwide. Current approaches to the development of murine models of SCA involve the elimination of functional murine ␣-and ␤-globin genes and substitution with human ␣ and ␤ s transgenes. Recently, two groups have produced mice that exclusively express human HbS. The transgenic lines used in these studies were produced by coinjection of human ␣-, ␥-, and ␤-globin constructs. Thus, all of the transgenes are integrated at a sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 36 publications
0
34
0
Order By: Relevance
“…However, it is present in the globin CH at all stages analyzed to date. In addition, it is also known that the upstream HS-111 (the equivalent of mouse HS-62.5/HS-60, Bulger et al 2003; also not present in all of the lines reported here) and downstream 3Ј HS1 are not required for a high level of expression of the ␤-globin locus when introduced in transgenic mice (Strouboulis et al 1992) and that such lines express at the same level as lines that contain the 5Ј and 3Ј flanking sites (Bungert et al 1995;Peterson et al 1996;Chang et al 1998;Calzolari et al 1999). At first sight, these data would suggest that the HSs involved in the CH complex formation are not very important, but why then would there be a CH?…”
Section: The 3-d Structure Of the Locusmentioning
confidence: 99%
“…However, it is present in the globin CH at all stages analyzed to date. In addition, it is also known that the upstream HS-111 (the equivalent of mouse HS-62.5/HS-60, Bulger et al 2003; also not present in all of the lines reported here) and downstream 3Ј HS1 are not required for a high level of expression of the ␤-globin locus when introduced in transgenic mice (Strouboulis et al 1992) and that such lines express at the same level as lines that contain the 5Ј and 3Ј flanking sites (Bungert et al 1995;Peterson et al 1996;Chang et al 1998;Calzolari et al 1999). At first sight, these data would suggest that the HSs involved in the CH complex formation are not very important, but why then would there be a CH?…”
Section: The 3-d Structure Of the Locusmentioning
confidence: 99%
“…The sickle cell anemia mouse line carrying a yeast artificial chromosome containing 240 kb of human ␤-globin gene cluster was used in these experiments (13). Female mice carrying homozygous or heterozygous mouse ␣-globin, heterozygous mouse ␤-globin gene knockouts, and homozygous human ␣-and ␤ S -globin yeast artificial chromosome transgenes were mated with male mice with the same genotype.…”
Section: Generation Of An Es Cell Line That Carries the Sickle Cell Amentioning
confidence: 99%
“…13. Briefly, 20 g of construct was linearized at the NotI site and electroporated into 3 ϫ 10 6 ES cells in 0.8 ml of Hepes-buffered saline in a 0.4-cm gap cuvette with a single pulse of 240 V and 125 F in a Gene Pulser (Bio-Rad).…”
Section: Gene Targeting and Identification Of Homologous Recombinantsmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Briefly, concentrated chromosomal DNA from the b S -YAC strain (AB1380 background) 21 was prepared and resolved on a 1% low-melt agarose pulsed-field gel at 200 V, 141C, 20-50 s, 33 h. The YAC was isolated, equilibrated with a modified agarase buffer (10 mM BisTris-HCl pH 6.5, 1 mM EDTA, 100 mM NaCl), treated with b-agarase I (New England Biolabs), and concentrated to a final volume of B200 ml. A volume of 30 ml of the purified YAC were introduced into competent LSY678IntHyg(rep) cells by spheroplast transformation and selection on agar/sorbitol plates lacking tryptophan.…”
Section: Yac Manipulationsmentioning
confidence: 99%